Developing a Project-Based Hyper-Content E-Module to Support Students’ Self-Regulated Learning in Higher Education - Agus Hadi Utama; Qomario (Jurnal Komunikasi Pendidikan, 2026)
This Research and Development (R&D) study aimed to develop a project-based learning (PjBL) hyper-content e-module to support students’ Self-Regulated Learning (SRL) in higher education. Utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research addressed the need for innovative digital resources in the Learning Resource Center Management Course at Educational Technology Study Program Lambung Mangkurat University. Unlike previous studies that focused on isolated variables, this research integrates development, PjBL implementation, and SRL impact analysis. The hyper-content e-module incorporates multimodal features, including audio, video, infographics, and QR codes, to facilitate independent exploration. Validation by experts yielded high feasibility scores: 89% from material experts, 87% from media experts, and 88% from instructional design experts. Through qualitative content analysis conducted during the analysis and evaluation phase, the results confirmed that the PjBL-integrated e-module effectively improved students' learning independence by providing structured, project-oriented digital pathways. The results confirm that the e-module is a feasible and effective tool for modernizing instructional delivery. This study contributes an innovative framework for digital resource management and provides a foundation for future applied research in enhancing educational quality through self-regulated, technology-enhanced learning environments.